Carcinoma‐associated fibroblasts derive from mesothelial cells via mesothelial‐to‐mesenchymal transition in peritoneal metastasis. Issue 4 (12th November 2013) - Sandoval, Pilar; Jiménez‐Heffernan, Jose Antonio; Rynne‐Vidal, Ángela; Pérez‐Lozano, María Luisa; Gilsanz, Álvaro; Ruiz‐Carpio, Vicente; Reyes, Raquel; García‐Bordas, Julio; Stamatakis, Konstantinos; Dotor, Javier; Majano, Pedro L; Fresno, Manuel; et al.
Abstract: Peritoneal dissemination is a frequent metastatic route for cancers of the ovary and gastrointestinal tract. Tumour cells metastasize by attaching to and invading through the mesothelial cell (MC) monolayer that lines the peritoneal cavity. Metastases are influenced by carcinoma‐associated fibroblasts (CAFs), a cell population that derives from different sources. Hence, we investigated whether MCs, through mesothelial–mesenchymal transition (MMT), were a source of CAFs during peritoneal carcinomatosis and whether MMT affected the adhesion and invasion of tumour cells. Biopsies from patients with peritoneal dissemination revealed the presence of myofibroblasts expressing mesothelial markers in the proximity of carcinoma implants. Prominent new vessel formation was observed in the peritoneal areas harbouring tumour cells when compared with tumour‐free regions. The use of a mouse model of peritoneal dissemination confirmed the myofibroblast conversion of MCs and the increase in angiogenesis at places of tumour implants. Treatment of omentum MCs with conditioned media from carcinoma cell cultures resulted in phenotype changes reminiscent of MMT. Adhesion experiments demonstrated that MMT enhanced the binding of cancer cells to MCs in a β 1‐integrin‐dependent manner. Scanning electron microscopy imaging showed that the enhanced adhesion was mostly due to increased cell–cell interaction and not to a mere matrix exposure. Invasion assays suggested a reciprocal stimulation of the invasive capacity of tumour cells and MCs. Our results demonstrate that CAFs can derive from mesothelial cells during peritoneal metastasis. We suggest that MMT renders the peritoneum more receptive for tumour cell attachment/invasion and contributes to secondary tumour growth by promoting its vascularization. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.